2014
DOI: 10.1111/srt.12172
|View full text |Cite
|
Sign up to set email alerts
|

Analytic parallel‐polarized light imaging technique using various light‐emitting diodes: a comparison with skin conductance values

Abstract: The correlations between CIELAB values and multiple characteristics of skin were more significant when green LED was applied than when white light was applied. In addition, coherent relationships between the grade of dryness and skin conductance values showed that visual assessment could be appropriate for the study as with objective measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…8 According to another study using LED illuminators of various colors, the green LED illuminator yielded more accurate and objective skin image data. 9 Thus, we chose to use the green LED illuminator as the light source in our study. We also used the conventional white LED illuminator in the study to compare the effectiveness of both green and white light.…”
Section: Discussionmentioning
confidence: 99%
“…8 According to another study using LED illuminators of various colors, the green LED illuminator yielded more accurate and objective skin image data. 9 Thus, we chose to use the green LED illuminator as the light source in our study. We also used the conventional white LED illuminator in the study to compare the effectiveness of both green and white light.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel-polarized light (PPL) photography is a method that can objectively evaluate reflections from the skin surface1. A preliminary study with various skin diseases indicated that PPL photography images taken with green light emitting diodes (LEDs) might be useful for analyzing specific diseases such as atopic dermatitis, rosacea, and xerotic dermatitis2.…”
Section: Introductionmentioning
confidence: 99%
“…Age‐associated skin color changes may be studied using colorimetric analyses using the CIE L * a * b * system (Kikuchi et al, ; de Rigal et al, ; Kim et al, ); our previous studies reported a significant correlation between colorimetric values and age (Kim et al, ). However, the extant literature does not document a correlation between skin color modifications and histologic findings, according to individual age.…”
Section: Introductionmentioning
confidence: 99%